The Impact of Fairness on Service Recovery to BRI Bank Customers Satisfaction and Loyalty on Pemalang Branch of Central Java - Chandra Arief Mauriat; Budi Astuti (Jurnal Manajemen dan Bisnis Indonesia, 2018)
The population used in this study is all customers of Bank BRI Branch Pemalang who do complaints. While this sample was 150 customers were considered to have been adequately represent the population studied. The sampling technique used purposive sampling method that is the customers who never make a complaint at Bank BRI. Analysis model used in this research is descriptive analysis, multiple linear regression analysis and simple linear regression analysis. The study found that 1) there is a positive and significant effect on the variable procedural fairness to the satisfaction of the recovery, 2) there is a positive and significant effect on the variable distributive fairness to the satisfaction of recovery 3) there is a positive and significant effect on the variable fairness interaction to the satisfaction of the recovery and 4) There is a positive and significant effect on the variable satisfaction on customer loyalty BRI Bank Branch Pemalang. The implication of this research is recommended to Bank BRI Branch Pemalang to pay attention to fairness in service recovery both procedural fairness, distributive fairness and interactional fairness to increase the satisfaction of the recovery so expect customer loyalty will increase, especially in providing the right solution in the handling of a complaint. Keywords: procedural fairness, distributive fairness, interactional fairness, loyalty